Asexual Reproduction of Black Sea Cucumber from Jepara Waters - Retno Hartati; Muhammad Zainuri; Ambariyanto Ambariyanto; Sri Redjeki; Ita Riniatsih; Ria Azizah; Hadi Endrawati (Marine Science Department Diponegoro University, 2019)
Black sea cucumber or Lollyfish are trade name for Holothuria atra, one species of family Holothuriidae abundance in Jepara waters, especially in Panjang Island. They inhabit on the seabed, in shallow waters on reefs and sand flats or in Seagrass meadows. Beside reproduce sexually, H. atra also do fission (biology), i.e. able to reproduce asexually by transverse fission. Monthly survey has been conducted for three months to determine frequency of fission among H. atra population in Panjang Island waters. In total 891 individu of H. atra inhabit in seagrass meadow mixed with rubble were examimed. In fissiparous sea cucumber, transverse fission are followed by regeneration and in this research identified from external observations. The fission state was divided into three category, i.e. closed wound (Category 1), little regeneration either posterior or anterior part (category 2), moderate regeneration either posterior or anterior part (category 3). The result showed that the fission frequency was highest during end of rainy season in April (13,21%) and decreased during May (4,61%) and June (4,86%). Body regeneration seem happened fast, since the new individu sea cucumber at category 1 was low but high as category 3. The regeneration were related with the condition of environment.